Prevalence of pulmonary edema among the deceased cases with acute Methadone poisoning: A report from Iran - Nastaran Eizadi-Mood; Seyed Amir Hossein Madani Naeini; Mahrang Hedaiaty; Ali Mohammad Sabzghabaee; Maryam Moudi (Wolters Kluwer Medknow Publications, 2016)
Objective: Methadone poisoning is common in our society, mainly in drug addicts. One of its lethal complications is pulmonary edema. Therefore, we evaluated the prevalence of pulmonary edema in the deceased cases with methadone poisoning and its possible relationship with some medical variables. Methods: In this cross-sectional study which was done in 2014, we have investigated the deceased patients with methadone toxicity who underwent autopsy at Isfahan Forensic Medicine Department (Iran). All variables including age, gender, and autopsy findings were recorded and analyzed. Demographic characteristics and medical complications of the patients were compared between the patients with or without pulmonary edema in the autopsy findings. Findings: There were 64 cases who died with methadone poisoning during the 1-year study period. The average age of cases (±standard deviation) was 32.1 ± 10.29 years, among which 92.2% were male. Based on the autopsy findings, 64.1% were diagnosed with pulmonary edema. There was no statistically significant relationship between pulmonary edema and age, gender, history of addiction, and hepatic or cardiovascular complications. Conclusion: Pulmonary edema is a common finding in deceased methadone poisoning cases and must be considered and ruled out in patients with acute methadone toxicity.